PENERAPAN METODE PIECES PADA PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PT VALLERY - Dhila Franzely Dhimas Putra; Adi Sopian (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
Along with the times and technology, computers are an electronic medium that plays a very important role, and continues to dominate various work processes in order to make it easier, more effective and efficient. PT. Vallery is a company engaged in the sale of fire extinguishers located in Jakarta. The orientation of this company is to meet the needs of the Indonesian people for practical, safe, environmentally friendly fire prevention and extinguishing devices that have received worldwide recognition. To smoothen its operations, it requires a system of selling goods that is right and able to attract consumers. PT. Vallery still experiences problems in presenting inventory reports and sales reports, because document storage is currently done manually using ledgers in the recording process. Searching for sales and inventory data takes a long time because you have to open the data stored in notes and ledgers, so that it has an effect on the slowness of the sales and reporting process.